2015
DOI: 10.1021/acs.analchem.5b03445
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Lipophilic Antioxidants of Olive Oils Using Bicontinuous Microemulsions

Abstract: Quantitative analyses of olive oil for lipophilic antioxidants, such as α-tocopherol and phenolics, by simple electrochemical measurements were conducted in a bicontinuous microemulsion (BME), which was bicontinuously composed of saline and toluene microphases with a surfactant system. Lipophilic antioxidants in oils were directly monitored in BME solutions using a lipophilic, fluorinated nanocarbon-film electrode (F-ECR). The combination of a well-balanced BME and extremely biased electrodes, such as strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…of rotation without any cosurfactant. Moreover, unlike the previously published reports [50][51][52][53][54] . we have also presented first visual evidence (TEM image) of olive oil sitting in the micellar cavity of the surfactant, PF 127 (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…of rotation without any cosurfactant. Moreover, unlike the previously published reports [50][51][52][53][54] . we have also presented first visual evidence (TEM image) of olive oil sitting in the micellar cavity of the surfactant, PF 127 (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Although olive oil has been extensively used as water in oil microemulsion (W/O) for various applications, there are few reports of its utility as oil in water (O/W) micro/ nanoemulsion [50][51][52][53][54] . These microemulsion were prepared using either co-surfactants or a number of chemical stabilizers using highly energy intensive procedures like ultrasonication and temperature induced phase inversion etc.…”
Section: Discussionmentioning
confidence: 99%
“…4 B while maintaining sufficient electrochemical activity for FcPMB. (vitamin E) in olive oil samples by using a bicontinuous microemulsion (BME) solution and can selectively detect lipophilic vitamin E 60,61 with no interference of L-ascorbic acid which is a well-known hydrophilic antioxidant.…”
Section: Analytical Sciencesmentioning
confidence: 99%
“…Indeed, Kuraya et al reported the selective and individual determination of hydrophilic and lipophilic antioxidants in the same BME solution. 11,12 Here, a hydrophobic fluorinated nanocarbon (F-nanocarbon) film electrode produced the oxidation current of lipophilic α-tocopherol (vitamin E, VE), but no oxidation peak for hydrophilic L-ascorbic acid (vitamin C, VC). In contrast, hydrophilic indium tin oxide electrode exhibited the oxidation response of VC but not of VE.…”
Section: Introductionmentioning
confidence: 99%